Changes in Light Reflectance and Extent of Thawing Loss after Extended Freezing with Breast Fillets from Late Marketed Broiler Males Using Population Representatives Having L* above and below the Median - Galobart, J.; Moran Jr., E.T. (International Journal of Poultry Science, 2004)
Skin-less boneless fillets obtained from 500 broiler males at 56 days of age exhibited a median 48h PM L* = 63.0. Ten samples randomly representing the population below (L* < 62.5, average = 60.4) and 10 above (L* > 63.5, average = 65.1) were held at -20°C for 5 months. Muscles were thawed 3 days at 4°C. Total drip was 10.7%, and similar losses occurred for samples above and below the 48h PM L* median. L* values measured on thawed fillets significantly decreased from their respective 48PM values with samples that had been located above the median but were similar with those below. Redness (a*) was similar among fresh samples, whereas a greater yellowness (b*) occurred with muscles having L* above the median than below it. Freezing led to increased a* and b* to the same extent after thawing. Light reflectance of fillets from late-marketed broilers indicates that PSE-like muscle would prevail with the population-at-large and uniformly exhibit associated problems.